Results of the Gestational Diabetes Mellitus Approach at the Center for Specialties in Women's and Children's Health in Itanhaem-SP (Research, Society and Development, 2018)
Documentary study of medical records of pregnant women with Gestational Diabetes sent to the high-risk prenatal center at the Center for Specialization in Women's and Children's Health - Cescrim "Paula Vegas". located in the city of  Itanhaem-São Paulo, Brazil, with the objective of identifying risk pregnancies during approach. From a total of 234 pregnant women enrolled in the PNAR-Prenatal High Risk system, 32 medical records were selected according to the research proposal, from September 2015 to June 2016, which were examined according to the following age, occupation, income, marital status, planned pregnancy, number of pregnancies, parity, abortions, stillbirths, type of birth, number of live births, date of last childbirth, gestational age, current weight, height, BMI, use of illicit substances fasting blood glucose at the beginning of prenatal, capillary glycemia control and oral glucose tolerance test (OGTT) of fasting and 2 hours. The obtained data were tabulated and placed in frequency tables. The specific results for the screening of DMG, indicated 59.3% for the first fasting glycemia between 92 and 125 mg / dl, thus confirming the suspicion of gestational diabetes. In the indeterminate results, the 2nd glycemia showed that 53% had altered results, showing the need to confirm the examination for early diagnosis of GDM. From the tests used as a coadjuvant for screening, such as Glucose Tolerance Testing, Capillary Glycemia, the results indicated 28% of the altered glycemic control, as well as Tolerance Test, with 2-hour glycemia, with 18.7% altered. The profile of the pregnant women, the risk factors for Gestational Diabetes, the methodology used to suspect the diagnosis, the conduct of the cases with confirmed criteria and the performance of the Nurses during the nursing consultation were also evaluated. It was evidenced the importance of care in the High Risk Specialized Referral Unit, which should be prepared to host the pregnant woman, promoting actions that will contribute to an early diagnosis, treatment, prevention of complications and solutions to problems and difficulties encountered during subsequent consultations, offering comprehensive and individualized humanistic and holistic care to pregnant women.